LBA13Clinical outcomes of ibrutinib in patients with relapsed or refractory mantle cell lymphoma: Korean multicenter, retrospective analysis. (24th November 2019) - Yi, J H; Kim, W S; Kim, S J; Yoon, D H; Suh, C; Chang, M H; Yang, D H; Jo, J-C; Hyun, S Y; Eom, H-S; Lee, J-O; Kwon, J H; et al.
Abstract: Background: Mantle cell lymphoma (MCL) is a distinct subtype of B-cell lymphoma and comprises approximately 5-10% of all lymphomas. However, in Korea, MCL accounts for just 2% of B-cell lymphomas. In addition to the paucity of the disease, due to lack of feasibility of novel agents for this disease, clinical outcomes of the novel agents have yet to be defined in Korea. Methods: We performed a retrospective study of MCL patients treated with ibrutinib in Korea. The primary endpoint of the analysis was progression free survival (PFS) out of ibrutinib treatment. Results: Between 2013 to 2019, a total of 75 cases were eligible for analysis. Median age at diagnosis was 69 (range, 40 – 90) and 61 patients (81%) were male. Most patients had an advanced disease at diagnosis (II 10, III 10, IV 55). The received induction regimens were as follows, R-CHOP (N = 48); R-HyperCVAD/MA (N = 10); R-bendamustine (N = 5); VR-CAP (N = 3); others (N = 9) At time of ibrutinib treatment, median age was 71 (range, 41-92), and the median number of prior treatments was 1 (range, 1 – 6). Eleven patients (15%) had received salvage autologous stem cell transplantation. Complete and partial responses were achieved in 31 (41%) and 22 patients (29%), respectively. At a median follow-up duration of 30.5 months (95% CI 25.9 – 35.1), the estimated median PFS was 18.6 months (95% CI 11.0 – 26.2). Those who were classified as low- or intermediated-risk MIPI score at the time of ibrutinib start (24.4 vs. 9.9 months, p = 0.031) demonstrated superior PFS, and patients with tumor size < 5 cm (25.5 vs. 9.4 months, p = 0.092) demonstrated trends for prolonged PFS. Among elderly patients (≥ 65 yrs), those who had received ibrutinib as the first salvage treatment showed significantly prolonged PFS compared to those who had received ibrutinib as the later line of treatment (24.4 vs. 5.8 months, p = 0.015). Conclusions: The response rate as well as the PFS data of the current study is similar to those of the Western reports. The current study provided additional evidence to support the use of ibrutinib in relapsed or refractory MCL, especially as the early salvage treatment. The compliance and safety data will be presented in the meeting. Funding: Janssen, Korea. Disclosure: All authors have declared no conflicts of interest.